The Effect of Tobacco Control Mass Media Campaigns on Smoking-Related Behavior Among People With Mental Illness: A Systematic Literature Review. Issue 11 (31st March 2022) - Perman-Howe, Parvati R; McNeill, Ann; Brose, Leonie S; Tildy, Bernadett E; Langley, Tessa E; Robson, Debbie
Abstract: Introduction: Tobacco control mass media campaigns (MMCs) can be effective generally, but little is known about their effects among people with mental illness. The objectives of this study were to systematically review: (1) Whether tobacco control MMCs affect smoking-related outcomes among people with mental illness. (2) Cost-effectiveness. Aims and Methods: Data sources: MEDLINE, Embase, PsycInfo, Web of Science, CINAHL, the Cochrane Library (searched March 2021), reference lists of included articles and relevant systematic reviews. Study eligibility criteria: Population: Adults with mental illness and experience of smoking tobacco and/or using other nicotine-containing products. Intervention/exposure: Tobacco control MMC messages. Comparator: No exposure, other tobacco control intervention(s), no comparator. Primary outcome: Changes in quitting behaviors. Study design: All primary research. Quantitative data were appraised using the EPHPP tool, qualitative data using CASP's Studies Checklist. Data were synthesized narratively. Results: Eight studies were included, seven were at high risk of bias. There was inconclusive evidence of the effect of MMCs on quit attempts and intentions to quit among people with mental illness. Increasing advertisement exposure did not increase quit attempts or intentions to quit among those with mental illness, however, increased exposure to an advertisement that addressed smoking and mental health did. None of the studies assessed cost-effectiveness. Conclusions: Findings should be interpreted with caution as data are limited and of low or moderate quality. There is evidence to suggest that tobacco control MMCs have limited impact on those with mental illness, although campaigns that are specific to smoking and mental health may be effective. Implications: There is a paucity of good-quality evidence of the effect of tobacco control MMC messages among people with mental illness. Careful consideration should be given to the design of future studies that evaluate MMCs in order to minimize the risk of bias, establish causality, and ensure the findings reflect real-world implementation. Further research should examine the need for MMC messages that address mental health.